PENGARUH REBUSAN DAUN KELOR TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS DI PANGARENGAN TAHUN 2022 - Ade Saputra; Solihati; Rina Puspita Sari (Yayasan Nusantara Hasana Berdikari, 2023)
The World Health Organization said that currently there are at least 150 million people who have diabetes worldwide. So do not be surprised if diabetes. is getting more and more attention because the number of sufferers continues to grow. Most sufferers admit that they only become aware of diabetes after serious complications arise such as eye problems or kidney problems. This study aims to determine the effect of moringa leaf decoction on reducing blood sugar levels in diabetes mellitus patients in Pangarengan in 2022. Research Village: the study used one group pre test and post test population of 45 people measuring variables at the same time. Sampling in this study used the Probability Sampling method with a simple random sampling technique with 30 respondents. Data analysis: As for data analysis in this study using univariate analysis of the results before being given Moringa leaf decoction, it can be concluded that the average blood sugar level before being given Moringa leaf decoction was 305.10 mg/dl and the standard deviation was 10,118 mg/dl, after given it was concluded that the average value of blood sugar levels before being given the moringa leaf decoction was 197.433 mg dl and the standard deviation was 12.048 mg dl and bivariate using the paired simples statistical test the standard deviation of blood sugar levels before being given the decoction and moringa was 107.67 mg/dl with standard deviation of 6,935 mg with stanistic obtained p value of 0.000 (p <0.05) 30 respondents. Results from the effect of boiling moringa daim on blood sugar levels in people with diabetes mellitus in Pangarengan p value = 0.000.